Synthesis and anti-enterovirus activity of new analogues of MDL-860. Issue 19 (1st October 2017) - Dobrikov, Georgi M.; Slavchev, Ivaylo; Nikolova, Ivanka; Stoyanova, Adelina; Nikolova, Nadya; Mukova, Lucia; Nikolova, Rosica; Shivachev, Boris; Galabov, Angel S.
Graphical abstract: Highlights: Analogues of diarylether MDL-860 were obtained. Some compounds possess in vitro antiviral activity against 3 enteroviruses, SI – up to 405 the most active compounds are low toxic. X-ray crystallography for the most active compound was performed. 3 Compounds showed promising in vivo activity. Abstract: A series of twelve novel compounds, analogues of antiviral agent MDL-860 were synthesized and their antiviral activity was evaluated in vitro against enteroviruses poliovirus 1 (PV1), Coxsackieviruses B1 (CVB1) and Coxsackieviruses B3 (CVB3). Compounds14, 24 and25 manifested strong antiviral effects against CVB1 and PV1 (SI values of 405 and 118 for CVB1 and PV1 respectively). In contrast to the wide anti-enteroviral activity of MDL-860, these three compounds were inactive against CVB3. Compounds14, 24 and25 along with MDL-860 were tested in vivo in mice infected with CVB1. Marked protective effects of compounds14 and24 were established, PI values of 50% and 33.3%, respectively. In addition, almost all of the tested compounds manifested very low toxicity.